Rett Syndrome: From Bed to Bench - Shih-Ming Weng; Mark E.S. Bailey; Stuart R. Cobb (Pediatrics and Neonatology)
Rett syndrome (RTT), a neurodevelopmental condition characterized by delayed-onset loss of spoken language and the development of distinctive hand stereotypies, affects approximately 1 in 10,000 live female births. Clinical diagnosis has been based on symptoms such as loss of acquired purposeful hand skills, autistic behaviors, motor dysfunctions, seizure disorders, and gait abnormalities. RTT is a genetic disease and is caused almost exclusively by mutations in the X-linked gene, MECP2, to produce a phenotype that is thought to be primarily of neurological origin. Clinical reports show RTT patients to have a smaller brain volume, especially in the cerebral hemispheres, and alterations in various neurotransmitter systems, including acetylcholine, dopamine, serotonin, glutamate, substance P, and various trophic factors. Because of its monogenetic characteristic, disruption of Mecp2 is readily recapitulated in mice to produce a prominent RTT-like phenotype and provide an excellent platform for understanding the pathogenesis of RTT. As shown in human studies, Mecp2 mutants also display subtle alterations in neuronal morphology, including smaller cortical neurons with a higher-packing density and reduced dendritic complexity. Neurophysiological studies in Mecp2-mutant mice consistently report alterations in synaptic function, notably, defects in synaptic plasticity. These data suggest that RTT might be regarded as a synaptopathy (disease of the synapse) and thus potentially amenable to rational therapeutic intervention.